Undetected Long-Term Hypothyroidism Caused by Hashimoto’s Thyroiditis with Severe Cardiac Complications – An Unusual Case of Child Neglect - Otto Schneider, Karl (Klinische Pädiatrie, 2021)
Neglect in childhood may often be undetected for a long time. Parents of patients of handicapped children are often unable to cope with multiple medical and psychological problems that exist with such patients despite support by the health services [Jacobi G, Dettmeyer R, Banaschak S, Brosig B et al. Child abuse and neglect: diagnosis and management. Dtsch Arztebl Int 2010; 107: 231–240]. This is especially true for patients with trisomy 21 because they frequently suffer from complex congenital heart disease, feeding difficulties and behaviour anomalies. Additionally, various degrees of hypothyroidism are very frequent in Down syndrome but rarely lead – as in our case – to a life threatening disease.